Gross Total Versus Subtotal Surgical Resection in the Management of Craniopharyngiomas. (October 2020) - Grewal, Maeher R.; Spielman, Daniel B.; Safi, Chetan; Overdevest, Jonathan B.; Otten, Marc; Bruce, Jeffrey; Gudis, David A.
Craniopharyngiomas (CP) are suprasellar tumors that can grow into vital nearby structures and thus cause significant visual, endocrine, and hypothalamic dysfunction. Debate persists as to the optimal treatment strategy for these benign lesions, particularly with regards to the extent of surgical resection. The goals of tumor resection are to eliminate the compressive effect of the tumor on surrounding structures and minimize recurrence. It remains unclear whether a gross total resection (GTR) or subtotal resection (STR) with adjuvant therapy confers a better prognosis. Chemotherapy and radiation therapy (RT) have been explored as both neoadjuvant and adjuvant treatments to decrease tumor burden and prevent recurrence. The objective of this paper is to review the risks and benefits of GTR versus STR, specifically with regard to risk of recurrence and postoperative morbidity. Aggregated data suggest that STR monotherapy is associated with higher rates of recurrence relative to GTR (50.6% ± 22.1% vs 20.2% ± 13.5%), while STR combined with RT leads to recurrence rates similar to GTR. However, both GTR and RT are independently associated with higher rates of comorbidities including panhypopituitarism, diabetes insipidus, and visual deficits. The treatment strategy for CPs should ultimately be tailored to each patient's individual tumor characteristics, risk, symptoms, and therapeutic goals.